Comparison of performance multi-platform application core on Android and Windows 10 Mobile. - Wieczorek, Dawid; Smołka, Jakub (Journal of Computer Sciences Institute, 2018)
The article examined whether applications written using the cross-platform application framework perform equally well as native solutions on selected operating systems. The Xamarin.Forms framework was tested against the native Android SDK and Universal Windows Platform frameworks for mobile systems Android and Windows 10 Mobile.